(untitled) (Annals of Medical Research, 2021)
Aim: Hysterectomy is generally used to treat patients with endometrial cancer. Although lymphadenectomy can provide prognostic information, there are serious complications that can result from lymph node dissection. In order to avoid unnecessary surgical intervention, predictors related to both pelvic and para-aortic lymph node metastasis can be identified. In this study, we sought to define independent prognosticators for pelvic and para-aortic lymph node metastasis in women with endometrial cancer.Material and Methods: In total, 284 patients who were treated surgically between December 2009 and January 2019 were included in the study. The relationships between histopathological patient characteristics and definitive lymph node status were studied.Results: In multivariate analysis, lymphovascular space invasion (Adjusted Odds Ratio: 4.8, 95% Confidence Interval 2.4–17.5, p = 0.001) and deep myometrial invasion (Adjusted Odds Ratio 3.8, 95% Confidence Interval 1.1–14.3) were independent factors for pelvic lymph node metastasis. In multivariate analysis for para-aortic lymph node metastasis, lymphovascular space invasion (Adjusted Odds Ratio 5.9, 95% Confidence Interval 2.1–10.3) and pelvic lymph node metastasis (Adjusted Odds Ratio 20.8, 95% Confidence Interval 8.9–32.3) were independent prognostic factors significantly associated with the presence of para-aortic lymph node metastasis. Conclusion: The two independent histopathological factors identified for predicting the presence of pelvic lymph node metastasis were lymphovascular space invasion and outer half myometrial penetration of the tumor. Lymphovascular space invasion and pelvic lymph node metastasis were independently associated with the presence of para-aortic lymph node metastasis. Consideration of lymphadenectomy in patients who have evidence of outer half myometrial invasion or pelvic lymph node metastasis on preoperative imaging may be prudent. Lymphovascular space invasion and myometrial invasion findings on frozen section can be used before proceeding with lymphadenectomy in endometrial cancer.